In House Training (IHT) Increasing Teacher Competencies in Building Literacy and Numeration Learning Strategies - Muhammad Soleh Hapudin; Mujazi Mujazi (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2024)
Literacy scores in the Curug District Public Elementary School Cluster are still relatively low. Therefore, the service team carried out service with the aim of increasing teacher competence in literacy and numeracy learning in the Curug District Public Elementary School Cluster environment. In House Training activity is a form of Community Service carried out by Esa Superior University PGSD Lecturers for Dirgantara Elementary School teachers in the Legok District Cluster area, Tangerang Regency. This activity was carried out as an effort to provide knowledge (insight) and increase teacher competence in developing literacy and numeracy-based learning strategies, so that they can be implemented in schools in the learning process. This activity will be held on September 25 and October 27 2023 in the Dirgantara Elementary School classroom, Legok District. The material presented is in the form of material exposure, simulations and practices carried out by IHT participants. This Community Service activity is a collaboration between lecturers and students of the Primary School Teacher Education Study Program (PGSD) at Esa Unggul University and the management of SDN Dirgantara. As a result of this activity, teachers have the ability to improve literacy and numeracy learning in schools. Therefore, it is concluded that the service activities carried out were successful in achieving the objectives.